2021
DOI: 10.14744/tjtes.2021.94799
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between admission neutrophil/lymphocyte, thrombocyte/lymphocyte, and monocyte/lymphocyte ratios and 1-year mortality in geriatric hip fractures: triple comparison

Abstract: BACKGROUND: Elderly patients with hip fractures have a high post-operative 1-year mortality rate. The aim of this study was to investigate the relationship of the neutrophil/lymphocyte ratio (NLR), thrombocyte/lymphocyte ratio (TLR), and monocyte/lymphocyte ratio (MLR) with mortality. METHODS:The data of 350 patients who suffered femoral intertrochanteric fractures between January 2015 and January 2020 were examined, and the demographic data of 124 patients who met the study criteria were evaluated. During the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
(44 reference statements)
1
6
0
Order By: Relevance
“…The PLR has emerged as a notable marker for systemic inflammatory response across various clinical scenarios, including fractures, oncological conditions, and instances of polytrauma. [22][23][24][25] Research indicates that significant trauma triggers heightened platelet activation, thereby initiating a cascade of coagulation and immune responses. [26] Wang et al corroborate this, demonstrating the postoperative PLR as a robust biomarker closely associated with the trauma severity in patients undergoing treatment for bicondylar tibial plateau fractures (TPFs).…”
Section: Discussionmentioning
confidence: 99%
“…The PLR has emerged as a notable marker for systemic inflammatory response across various clinical scenarios, including fractures, oncological conditions, and instances of polytrauma. [22][23][24][25] Research indicates that significant trauma triggers heightened platelet activation, thereby initiating a cascade of coagulation and immune responses. [26] Wang et al corroborate this, demonstrating the postoperative PLR as a robust biomarker closely associated with the trauma severity in patients undergoing treatment for bicondylar tibial plateau fractures (TPFs).…”
Section: Discussionmentioning
confidence: 99%
“…The platelet-to-lymphocyte ratio (PLR) is becoming recognized as an indicator of systemic in ammatory response in fractures, malignant tumors, and polytrauma. [23][24][25][26] The previous study has shown that signi cant trauma often leads to increased platelet (PLT) activation and activity, initiating the coagulation cascade and immunological reactions [27]. Wang et al [23] found that postoperative PLR seems to be a valuable biomarker that correlates strongly with the severity of surgery-related trauma in patients with bicondylar TPFs.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Moreover, previous studies have revealed that admission NLR value could be a prognostic factor for 1-year mortality in elderly patients with hip fracture. 10,20 And also, MLR has been suggested to be associated with poor survival in elderly patients with hip fracture. 8,21 The NLR and MLR are additional inflammationbased markers that have been widely studied in various medical conditions, including cardiovascular diseases and cancer.…”
Section: Inflammation Predict Long-term Mortality After Hip Fracture ...mentioning
confidence: 99%
“… 10 , 20 And also, MLR has been suggested to be associated with poor survival in elderly patients with hip fracture. 8 , 21 The NLR and MLR are additional inflammation‐based markers that have been widely studied in various medical conditions, including cardiovascular diseases and cancer. Both ratios are calculated by dividing the absolute count of neutrophils or monocytes, respectively, by the absolute count of lymphocytes.…”
Section: Inflammation Predict Long‐term Mortality After Hip Fracture ...mentioning
confidence: 99%